Evaluation of the Monetary Value of Air Pollutants’ Reduction by Forests in South Korea - Sumin Choi; Jinsuk Jeong; Chan-Ryul Park (Forest Science and Technology)
The economic value of forests as public goods is often underestimated. This study evaluates the public benefit of air quality improvement by forests in South Korea from 2014 to 2020. The monetary value of air quality improvement, particularly in five air pollutants (i.e., SO2, NO2, PM10, PM2.5, and O3), has gradually increased from KRW 6.0767 trillion in 2014 to KRW 6.5511 trillion in 2017. However, the value decreased from KRW 5.8712 trillion in 2018 to KRW 5.2597 trillion in 2020, possibly due to a decrease of forest area and air pollutant concentrations. In 2020, following the COVID-19 pandemic, the concentrations of air pollutants decreased remarkably from the previous year. For a more objective assessment, it is necessary to examine the total area of green space, including green facilities and urban forests, which are not included in the national data used in the study. Furthermore, key assessment items such as the percentage of vegetation cover, deposition rate, and pollutant removal costs should be modified and adapted to domestic conditions. To this end, monitoring data on the air quality impacts of forests should be utilized in order to facilitate the study of the air quality improvement function of forests at different temporal and spatial scales.